Effect of digestion and thermal processing on the stability of microbial cell-aflatoxin B1 complex. (May 2021) - Sohrabi Balsini, Mohammad; Edalatian Dovom, Mohammad Reza; Kadkhodaee, Rassoul; Habibi Najafi, Mohammad Bagher; Yavarmanesh, Masoud
Abstract: This study investigates the removal of aflatoxin B1 by viable and heat treated cells of Saccharomyces cerevisiae (PTCC 5052) and Lactobacillus rhamnosu s GG (ATCC 53103) in a model system as a function of time and salt concentration. Moreover, the stability of microbial cell-aflatoxin B1 complex was evaluated at elevated temperature, high shear stress as well as under simulated digestive conditions. The rate of aflatoxin B1 adsorption was found to be significantly different for viable and heat treated cells. Heat inactivation of L. rhamnosus GG and S. cerevisiae dramatically increased the rate of toxin adsorption to 97.74% and 92.34%, respectively. Desorption of aflatoxin B1 from L. rhamnosus GG was approximately 3 times greater than viable S. cerevisiae and nearly1.5 times higher than heat treated cells. The maximum desorption of aflatoxin B1 from complexes occurred after 3 h incubation in simulated intestinal fluid. Shear stress and simulated saliva had no impact on the breakage of cell-aflatoxin B1 complex. The complexes formed by heat treated cells exhibited high stability against thermal treatment, whilst those generated by viable strains experienced toxin release during heating, which was much higher for S. cerevisiae (%4.68) than L. rhamnosus GG (%0.99). Highlights: AFB1adsorption was influenced by temperature and salt concentrations in LAB and yeast . Toxin adsorption behavior was affected by physicochemical factors at different times. Type of microbe and its state has an impact on microbe-AFB1complex stability. Microbe-AFB1complex stability was evaluated in different gastrointestinal simulation conditions. Microbe-AFB1complex stability was influenced by heating and mechanical stress.